Frailty and Neurocognitive Impairment: Impacts on Quality of Life in HIV. (May 2020) - Rubtsova, Anna A.; Sabbag, Samir; Sundermann, Erin; Nguyen, Annie L.; Ellis, Ronald J.; Moore, David J.; Letendre, Scott; Jeste, Dilip V.; Marquine, María J.
Abstract: Little is known about the effects of aging-related conditions on health-related quality of life (HRQOL) among people living with HIV (PLWH). The purpose of our study was to examine the independent effects of neurocognitive impairment (NCI) and frailty and the interactive effects with HIV serostatus on HRQOL. Our sample consisted of 121 adults (63 PLWH and 58 HIV-uninfected) participating in the Multi-Dimensional Successful Aging among HIV-Infected Adults study at the University of California, San Diego. HRQOL was measured with the Medical Outcome Study 36-Item Short Form Health Survey scale. We found that frailty was significantly associated with HRQOL ( p < .001) in the overall sample, and this effect was significantly stronger for PLWH than HIV-uninfected adults. NCI was not significantly associated with HRQOL in our sample. Frailty may be a particularly important factor in HRQOL for PLWH, highlighting the need for prevention and intervention strategies to mitigate the risks for frailty.